Modification of Mg/Al-LDH Intercalated Metal Oxide (Mg/Al-Ni) to Improve The Performance of Methyl Orange and Methyl Red Dyes Adsorption Process - Nova Yuliasari; Arini Fousty Badri; Alfan Wijaya; Patimah Mega Syah Bahar Nur Siregar; Amri; Mardiyanto; Risfidian Mohadi; Aldes Lesbani (Science and Technology Indonesia, 2022)
Modification of Mg/Al-LDH intercalated metal oxide (Mg/Al-Ni) was successfully formed by the coprecipitation method at pH 10, which is indicated by the XRD diffraction, FTIR spectrum, and BET analysis. Mg/Al-LDH increased surface area after intercalated Ni from 8.621 m2/g to 9.821 m2/g and improved performance in process regeneration which can be used in the three cycles. Mg/Al-LDH after intercalated metal oxide (Ni) increases adsorption capacity of is 69.930 mg/g to 71.429 mg/g for methyl orange (MO) and 77.519 mg/g to 98.039 mg/g for methyl red (MR). Equilibrium time on the adsorption process occurred at 90 minutes with adsorption kinetics followed pseudo-second-order (PSO). Thermodynamic parameters indicate that the adsorption process is spontaneous and endothermic with the physical adsorption process.